Pengaruh Manajemen Risiko Terhadap Nilai Perusahaan - Andina, Ariane Satri; Indriani, Rini; Suranta, Eddy (JURNAL FAIRNESS, 2013)
This study investigates the significant impact of ERM programme to firm value and its implication for enterprise itself and also the differences of firm value between ERM’s degree of implementation. ur attention in this study on Indonesia’s non-finance enterprise in order to control for differences that might arise from regulatory and characteristic of market differences across industries. Using finance risk as ERM’s proxies, The test was made into 2 phase by include and exclude size as variable control into a model. The result shows that there is positif significant impact of capital risk to firm value and positive significant risk between credit risk and firm value. We also found that there are differences of firm value between We cant prove the impact of foreign exchange risk, and hedging risk to firm value. We also find that contradictive result when sample is divided based the degree of ERM’s implementation. Resulting of the findings, the authors proposes the identification of specific components and processes of ERM that contribute to firm value and evaluation of added benefit of ERM.